Systematic Review on Implication for DNA Assisted Technology into Molecular Medicine and the useful is the application of Genome Wide Studies - Fahmida Khatoon, Reem Ayed Alshammari, Aasma Batool, Abeer Hassan Elhaj, Fatmah Fahad Alreshidi, Gamal Eldin Mohamed Osman Elhussein, Rania Abdeen Hussin Abdalla, Amel Bakri Mohammed Elhag, Zahid Balouch, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The aim of this study is to explore the role of molecular DNA, DNA Phenotyping and Polymerase Chain Reaction in samples relevant to genetic investigation. The Deoxyribonucleic Acid (DNA) is a macromolecule which has propelled our capacity of understanding the function of an organism at the cellular level, how organism reproduce and replicate, and pass their subjective genetic information from one generation to the other. DNA is also referred to as the genetic “Blueprint” of an organism and found to possess all information pertaining to the specific being. Nuclear DNA is present within the nucleus and is significant in developing immunity for the cell and depends on the information incorporated within its framework. Mitochondrial DNA exists in varying locations in frequencies of two to ten copies within mitochondria. The most familiar body fluids come across in molecular medicine laboratories is blood, semen and saliva and further more are vaginal fluids, urine and sweat. Bones, teeth, soft tissues etc. are also essential biomarkers for DNA-phenotyping. Methodology: The methods for research for this particular study is to demonstrate a review of relevant literature to examine the molecular genetics and the application of genome and DNA-amplification into molecular medicine investigations. To conduct a literature review a qualitative research design is the most suitable research design. It provides the rationale for assessing the human behaviour and assists to legalize and authenticate the data which is selectively collected from the secondary sources. Results: Every individual’s DNA consists of minor alterations a change in these restriction places would result in different profile of restriction fragments. Genome wide population substructure is large enough to determine ancestry with large number of Autosomal SNPs at the level of continental resolutions. Conclusion: The advances in human genomics and molecular genetics have provided success and advances by determining the cellular origin and estimating the age of sample and disposition time. The Phenotypical characteristics like hair and eye color demonstration in criminal cases has yielded better inferences however, DNA phenotyping illustrates a limited approach wherein incorporated into biological material analysis. The accuracy of DNA technology is incredibly useful for professionals like lawyers, anthropologists, homicide detectives etc. in the field of molecular medicines and is expected to improve in years to come. Key Words; Deoxyribonucleic Acid (DNA) , Polymerase Chain Reaction (PCR), Mitochondrial DNA (mtDNA) sequencing and Short Tardem Repeat (STR)